Cities, classes, and the social order - Leeds, Anthony, 1925- (Anthropology of contemporary issues., 1994)
"Cities, Classes, and the Social Order brings together nine conceptual and theoretical essays by a leading anthropologist, Anthony Leeds (1925-1989). Leeds's pioneering work in the anthropology of complex societies was built on formative personal and research experiences in both urban and rural settings in the United States, Brazil, Venezuela, and Portugal. Inspired by Karl Marx and Alfred Kroeber, he developed a protean vision of culture, power, and the social order, and his work represents an outstanding synthesis that is relevant to current attempts at reintegrating a balkanized anthropology and to other social and human sciences." "Leeds brought to his anthropology a simultaneous concern for science and humanism, and for explanation and interpretation. He constructed a nuanced and intricate vision of the connections among ecology, technology, history, evolution, structure, process, power, culture, social organization, and human creativity. The essays in this book draw on his approach to demarcate the role of cities in human history, the use and abuse of class analysis, the bases of power in complex societies, and an agenda for ethnographic and social-historical research in the contemporary world." "In addition to major but little-known writings and an important essay on Marx here published for the first time in English, a selection of Leeds's ethnographically and politically inspired poems are included, as are several of his professionally exhibited photographs. In addition, introductory essays by R. Timothy Sieber and Roger Sanjek chart the course of Leeds's career and the development of his theoretical viewpoint."--Jacket